Childhood and youth of an intellectual: Harriet Martineau and 19th century British society - Alcântara, Fernanda Henrique Cupertino (Latitude, 2025)
(English translation by Renata Dermenjian - Tradução para o inglês de Renata Dermenjian) This article discusses childhood and youth as elements of social analysis based on autobiographical and biographical accounts of Harriet Martineau. It problematizes these accounts as characteristic of modernity and the advance of individualism, while at the same time valuing such sources as a reflective element and as a creator of a narrative about the history of the subject being discussed, through the method of bibliographic and descriptive research. It concludes on the importance of such accounts for understanding the production of each intellectual, as well as the contingent references related to the period and the circumstances in which they lived.